Upaya Guru Dalam Meningkatkan Kemampuan Mengenal Warna Melalui Media Krayon di PAUD Raudotul Zannah Pagaran Bira Julu Kecamatan Sosopan (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Based on the results of the research carried out by the author, it can be concluded that (1) The ability to recognize colors of early childhood in PAUD Raudotul Zannah is not yet optimal, as seen from the results of Not Developing (BB) of 10 children or 62.50%, the ability to recognize colors is Starting to Develop (MB) 5 children or 31.25%, ability to recognize colors developed according to expectations (BSH) 1 child or 6.25%, while ability to recognize colors developed very well (BSB no children. 2) Teacher's efforts to improve ability to recognize colors through crayon media in PAUD Raudotul Zannah Pagaran Bira Julu, Sosopan District, it has improved after action was taken with the results of Cycle I obtaining a score of Not Developed (BB), no children, ability to recognize colors Starting to Develop (MB) 8 children or 50.00%, ability to recognize colors Developing Appropriately Hope (BSH) 6 children or 37.50%, while the ability to recognize colors is very well developed (BSB) 2 children or 12.50%. And in cycle II, the results were Not Developed (BB), there were no children, the ability to recognize colors was Starting to Develop (MB), there were no children, the ability to recognize colors was Developing According to Expectations (BSH) 7 children or 43.75%, while the ability to recognize colors was Very Developed Good (BSB) 9 children or 56.25%. So it can be concluded that using crayon media can improve children's ability to recognize colors in PAUD Raudotul Zannah Pagaran Bira Julu, Sosopan District.